2020
DOI: 10.1007/s12103-020-09574-w
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Family Violence Are Not Causally Associated with COVID-19 Stay-at-Home Orders: a Commentary on Piquero et al.

Abstract: COVID-19 has caused a wave of research publications in academic and pre-print outlets which have resulted in several high-profile retractions. While the breadth of emerging research has been instrumental in understanding and curbing the global pandemic in near real-time, unfortunately manuscripts with major methodological challenges have fallen through the cracks. In this perspective, we illustrate this issue in light of a recent manuscript by Piquero et al. (2020). In the study, a statistically significant as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…A pesar de los limitados precedentes, algunas investigaciones (Campbell, 2020) indican que los efectos de las pandemias son sobre todo rápidos, con un aumento de la presión, cambios repentinos en el trabajo diario, cierre de las escuelas y los recursos comunitarios, y en general una reducción de los recursos disponibles. Montenegro y Montenegro (2020) manifestaron que las situaciones de vulnerabilidad de las poblaciones con menos recursos se agravaron con la pandemia derivada por el Covid-19 sobre todo por la pérdida de empleos, la precarización laboral, la alteración de las rutinas diarias, el mayor número de episodios de ansiedad y depresión, el crecimiento de adicciones, el aumento de casos de violencia doméstica e intrafamiliar en mujeres, niñas, niños y adolescentes, y en casos más graves femicidios, todo esto pese a que algunos autores cuestionaran la evidencia científica de que el confinamiento causara un aumento de la violencia de género (Reingle- Gonzalez et al, 2020).…”
Section: Resultsunclassified
“…A pesar de los limitados precedentes, algunas investigaciones (Campbell, 2020) indican que los efectos de las pandemias son sobre todo rápidos, con un aumento de la presión, cambios repentinos en el trabajo diario, cierre de las escuelas y los recursos comunitarios, y en general una reducción de los recursos disponibles. Montenegro y Montenegro (2020) manifestaron que las situaciones de vulnerabilidad de las poblaciones con menos recursos se agravaron con la pandemia derivada por el Covid-19 sobre todo por la pérdida de empleos, la precarización laboral, la alteración de las rutinas diarias, el mayor número de episodios de ansiedad y depresión, el crecimiento de adicciones, el aumento de casos de violencia doméstica e intrafamiliar en mujeres, niñas, niños y adolescentes, y en casos más graves femicidios, todo esto pese a que algunos autores cuestionaran la evidencia científica de que el confinamiento causara un aumento de la violencia de género (Reingle- Gonzalez et al, 2020).…”
Section: Resultsunclassified
“…First, WFH had a positive association with spending time with family members. This could be due to WFH eliminating the need to commute to the office, allowing workers to spend more time at home ( 19 , 28 , 29 , 33 ). Workers can benefit from the saved traveling time and flexible schedules to spend more time accompanying their family members.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case for highly educated workers, who tended to report spending less time with family members during WFH. Strategies to increase the interaction with family members include fostering communication with them ( 44 ), developing a positive family atmosphere ( 78 ), and investing more time and attention in homeschooling ( 29 ). Second, strategies should be provided to younger workers who perceived worse work-life balance during WFH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And Ashby ( 2020 ) found that most crime types decreased across 16 cities in the USA. Specifically, in the context of domestic violence, Piquero et al ( 2020a ) observed an immediate spike during the initial lockdown, followed by a decline in Dallas, TX, but there has been debate regarding these results (Reingle Gonzalez et al, 2020 ; Piquero et al, 2020b )—a more recent meta-analysis has shown domestic violence increased during the early stages of the pandemic (Piquero et al, 2021 ).…”
Section: Related Researchmentioning
confidence: 99%